Successful management of temporomandibular joint ankylosis after relapse in childhood - Bezerra, Tacíria Machado; Braga, David Nascimento; Alves, Thais Pinto; Lemos, Daniel; Cavalcante, Maria Aparecida; Castro, Gloria Fernanda (Revista de Ciências Médicas e Biológicas, 2017)
Objective: to describe the successful surgical management of a reankylosis in a 9 years old girl. Case report: when the patient was 3 years old she underwent arthroplasty of the right temporal muscle but presented a relapse due to the lack of cooperation during physiotherapy. The oral exam revealed a severe limitation of mouth opening (0.0mm), low weight for her age (19kg-P10%), bad oral hygiene and difficulties in socializing. The child was submitted to excision of the ankylotic mass and resection of the condyle (condylectomy) and reconstruction with a costochondral graft followed by aggressive postsurgical physiotherapy. After 7 months of specialized and home physiotherapy, the patient presented a mouth opening of 25 mm, and had increased weight significantly. Conclusion: the correct follow up was essential for the success of the surgical intervention and improvement in the child’s quality-of-life.